Plasma insulin levels in patients with ischemic heart disease with the different degree of atherosclerotic lesions of coronary arteries - G. Mankovsky; E. Stepura (Ukrainian Journal of Cardiovascular Surgery, 2017)
The aim of the study is to investigate the plasma insulin levels in patients with ischemic heart disease (IHD) and different degree of atherosclerotic lesions of coronary arteries Materials andMethods We examined 78 patients with IHD without history of diabetes mellitus or impaired glucose tolerance. All studied patients underwent stress test, coronaroventriculography and oral glucose tolerance test. The blood was collected at fasting and 2 hours after glucose ingestion. Insulin levels were determined in all blood samples by radioim-munosorbent method (ELISA) along with plasma glucose measurements.Results and Discussion. All studied patients with IHD were divided to 3 groups according to the number of occluded coronary arteries. None of the studied patients had type 2 diabetes mellitus or impaired glucose tolerance. The mean plasma glucose levels were 6,31±0,21 mMol/L, 5,78±0,15 mMol/L и 5,74±0,26 mMol/L at fasting and 2 hours after glucose inges-tion – 8,15±0,60 mMol/L, 8,56±0,47 mMol/L, 7,26±0,61 mMol/L in patients with 1, 2 or 3 occluded coronary arteries, respectively, р>0,05. Also, there was no elevation of glycated hemoglobin levels. It was found that plasma insulin levels were significantly elevated in patients with IHD and atherosclerotic lesions of 2 or 3 coronary arteries compared to patients with 1 occluded artery.Conclusions. Hyperinsulinemia as the reflection of insulin resistance is related to the more severe angiographically documented atheroclerotic lesions of coronary arteries in patients with IHD.